Pengembangan Screening Assessment untuk Meningkatkan Kompetensi Guru dalam Mengidentifikasi Perkembangan Bahasa Anak Usia Dini - Irayana, Ika (Indonesian Journal of Islamic Early Childhood Education, 2017)
This research aimed to: (1) produce the feasible screening assesment to increase PAUD teachers competition in identifiying language development of early childhood (2) know the effectiveness of screening assesment to increase PAUD teachers competition in identifiying language development of early childhood. This research is a research and development which is used Borg and Gall (2007) adapted from Dick and Carey. Stages included in this research and development are (1) Identification Instructional Goal, (2) Conduct Instructional Analysis, (3) Analyze Learners and Contexts, (4) Write Performance Objective, (5) Develop Assessment Instrument, (6) Develop Instructional Strategy, (7) Develop and Select Instructional Materials, (8) Design and Conduct Formative Evaluation of Instruction, (9) Resive Instruction, and (10) Design and Conduct Summative Evaluation. Feasiblity determination of screening assesment level was based on the experts validation test, individual trial and small group trial. Effectiveness determination of screening assesment level was based on the field trial. The reaserch performed on 30 teachers in Gugus of Kecamatan Banjarmasin Timur.Validation product result showed that screening assesment feasibled to increase the PAUD teachers competention in identifying language development. Wilcoxon test result that significance value was 0.000, which was smaller than 0.05 as the significance level used in this research, than H0 rejected and H1 accepted. Thus, concluded that the developed screening assesment product was increased PAUD teacherâs competence in identifying language development of early childhood.